RULE BASED MACHINE LEARNING FOR EXPLAINABILITY OF RESULTS IN COMPLEX LITHOLOGY CLASSIFICATION - HOSSAIN, TOUHID MOHAMMAD (2021)
With the advancement of machine learning, the automated estimation of complex lithology has become one of the most crucial requirements in petroleum engineering because of its important role in reservoir characterization.